The Effectiveness Of Using Flipped Classroom In Teaching Writing Descriptive Text - Efa Almania (Universitas Muhammadiyah Enrekang, 2022)
Writing is a communication tool or means of conveying information in writing. Writing activity is a form of expressing thoughts and feelings, arranged into words, sentences and paragraphs. This study aims to investigate the effectiveness of flipped classroom in teaching writing descriptive text. The research subjects at SMKN 1 Grogol, consisted of 26 students of accounting class 1 as the control group and class X accounting 2 consisting of 27 students as the experimental group. The research design used a quasi-experimental approach with a quantitative approach. The instrument used was a writing test consisting of a pretest and posttest in the experimental and control classes. Data analysis using ANCOVA through SPSS 21. Results The research findings prove that the ANCOVA results obtained a significance value of 0.000 which is smaller than 0.05. It means that the alternative hypothesis (Ha) is accepted, that there is a significant difference between the experimental and control groups. So, flipped classroom shows a significant effect on students' writing ability. Then, the average results show that using the flipped classroom method has a higher average. concluded that the flipped classroom effective in teaching writing descriptive text.